An analysis of the academic literature on fake news during Covid-19 pandemic / Noor Rahmawati Alias... [et al.] - Alias, Noor Rahmawati; Md Radzi, Salliza; Ahmad Zukarnain, Zuriani; Hamidon, Huda; Arifin, Noorfadzilah (Universiti Teknologi Mara Cawangan Kelantan, 2020)
Covid-19-related fake news has brought many negative impacts in the global community in many different aspects. The spread of the novel coronavirus which initially started in 2019, and that later was announced as a pandemic by the World Health Organisation (WHO), has resulted in the emergence of infodemic causing difficulties to governments and subjects. This study was carried out to identify the subject areas of research ever conducted which related to fake news on Covid-19 and the impacts caused by this false information phenomenon. Literature analysis of documents published in the SCOPUS online database has been conducted and it was found that previous research on Covid-19-related misinformation occurred in multiple subject areas of which are prominent in the medicine and social sciences field. The impact of this infodemic ranges from health, political, legal, and other social effects. It can be concluded that in order to minimise the confusion and risks of the infodemic, the digital and health literacy of the citizen has to be improved, apart from the government responsibilities and social media providers monitoring and controlling the dissemination of falsehood and rumours among various parties